Encyclopedia of immigration and migration in the American West - Bakken, Gordon Morris; Kindell, Alexandra; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2006)
These two volumes provide a complete history of racial and ethnic groups that have populated the American West, including the settling of the West and the movements of American Indians African Americans and the role of women in the West's development.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Migration, Internal -- West (U.S.) -- History -- Encyclopedias; Indians of North America -- West (U.S.) -- Encyclopedias; African Americans -- West (U.S.) -- Encyclopedias; Immigrants -- West (U.S.) -- Encyclopedias; Ethnology -- West (U.S.); Pioneers -- West (U.S.) -- Encyclopedias; West (U.S.) -- Emigration and immigration -- Encyclopedias; Electronic books